"We're Essential Because You're Essential": How Louisiana Sexual Assault and Domestic Violence Organizations Adapted Outreach Efforts and Health Messaging during COVID-19. Issue 3 (4th May 2022) - Ramirez, Fanny; Harris, Rockia
ABSTRACT: Within weeks of the World Health Organization declaring the COVID-19 outbreak a global pandemic, domestic violence and sexual assault incidents increased. To adhere to new health protocols, social service providers were encouraged to move outreach efforts to virtual formats. We draw on 21 in-depth interviews with Louisiana organizations working in violence against women to examine how they 1) transitioned to online outreach efforts and 2) adapted their messaging to the COVID-19 context. We found that organizations who successfully moved to virtual efforts credited their success to thinking creatively and properly matching educational activities to digital media platforms, while those who struggled pointed to obstacles such as digital media fatigue and funding limitations (RQ1). We also identified three changes to message framing (RQ2): 1) Empathy and reassurance, especially, reiterating that centers "are there" for victims 2) Addressing racial justice issues, and 3) describing COVID-19 protocols and conducting lockdown-focused education efforts.